PENERAPAN DEEP LEARNING BERBASIS CNN UNTUK MEMPREDIKSI PERILAKU PENGHINDARAN PAJAK WAJIB PAJAK BADAN - Mohamad Fahmi Yusuf; Bayu Malikhul Askhar; Rita Nataliawati; Qosim (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
Tax evasion by Corporate Taxpayers is a significant challenge for state revenue. This study aims to develop a tax evasion behavior prediction system using a deep learning approach based on Convolutional Neural Network (CNN). The objects of this study were 50 Corporate Taxpayers registered in Lamongan Regency during the period 2021 to 2024. The data used are secondary data from the manufacturing, trade and service sectors which include financial indicators such as Effective Tax Rate (ETR), total assets and reporting compliance. The data is then labeled into two categories, namely